Granting of Ownership Rights to Shophouses Following the Issue of Regulation of The Minister of Agrarian and Spatial Planning/Head of The National Land Agency of The Republic of Indonesia number 18 of 2021 - Frans Rian; Rita Armelia (West Science Law and Human Rights, 2023)
In the past, shophouses were not eligible for ownership rights as they were primarily designated for commercial purposes, whereas ownership rights were exclusively granted for residential properties.   Nevertheless, during its evolution, shophouses can also serve as dwellings.   This is deemed to be inconsistent with the philosophical underpinnings of property rights, which are solely intended for domestic use.   The subject addressed in this article pertains to two main aspects: the characteristics of property rights in Indonesia and the characteristics of property rights specifically related to shop houses.   The research methodology employed in this work involves legal research utilizing statutory and conceptual approaches.   The findings in this article are primary.   Property rights in Indonesia are characterized as hereditary, with the highest level of strength and comprehensiveness.  Furthermore, ownership of shophouses can be established through property rights, subject to the following conditions: obtaining permission to use the land and building for both residential and commercial purposes, having valid or expired Building Use Rights or Use Rights, and/or having the rights holder’s name registered alive or deceased.